The logic of formatting: A case study on transnational television production. Issue 3 (1st October 2021) - van Keulen, Jolien; Krijnen, Tonny; Bauwens, Joke
The transnationalization of television production has been examined by studies on formats and multinational media companies, which have often highlighted the resilience of the local in the global. This article investigates transnationalization on the micro level of television production, drawing on participant observations in a Dutch production company that is partly owned by an American conglomerate. It explores the deep entanglement of the local with the global in different facets of production ‐ including legal, organizational and market aspects ‐ as manifested in daily practices and decision-making in television production. Our analysis reveals an industrial logic of formatting that is not only induced by transnational ownership structures and business models but also deeply ingrained in production routines and programme conventions. Through this logic, transnationalization shapes media professionals' daily work, the selection of programme ideas and the process of content development.